Jurnal Ekonomi Syariah dan Ketah URGENSI PENCEGAHAN PERNIKAHAN DINI DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH: MENINJAU KESIAPAN FINANSIAL DAN DAMPAKNYA PADA MASA DEPAN GENERASI MUDA: Studi Kritis terhadap Implikasi Pernikahan Dini terhadap Stabilitas Finansial Keluarga dan Kesejahteraan Generasi Muda dalam Bingkai Hukum Ekonomi Syariah - Ariza, Aula Nur; Ahmad Faizi, Ahmad Faizi; Maydita, Fifa Lutfiana (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2025)
Child marriage remains a serious social issue in Indonesia, as observed in Pare, Kediri Regency, despite Law No. 16 of 2019 setting the minimum age for marriage at 19 years. This phenomenon is triggered by various factors such as economic pressure, low educational attainment, and cultural and family norms. The negative impacts of child marriage are highly detrimental, including health risks such as pregnancy and childbirth complications, limited access to education, psychological distress, and financial instability. From the perspective of Islamic economic law (hukum ekonomi syariah), financial readiness is a crucial aspect for household sustainability and well-being, as emphasized in the principle of al-qudrah 'ala an-nafaqah. Therefore, the socialization activities on preventing child marriage carried out by Hasyim Asy'ari University students at SMP Negeri 3 Pare are a strategic step to equip adolescents with an understanding of the importance of delaying marriage until an ideal age and achieving comprehensive readiness, including economic aspects, to secure the future of the younger generation.